Children’s right in custodial disputes: the extent of the application of best interest of the child principle under the Malaysian laws - Che Soh @ Yusoff, Roslina (2015)
Best interest of the child is the utmost fundamental right of children which is applicable to all matters relating to children for the purpose of safeguarding their well-being. In child custodial disputes, the tremendous shift from parental rights to parental responsibilities throughout the centuries had made the principle of best interests of the child as the utmost matter which the parents and judges must uphold. Although the commitment to this principle is significantly enshrined in the United Nation Convention on Rights of the Child and being mandated in the custody legislations of most nations in the world, the content and application of the principle differs across borders. Differences persist notwithstanding many countries have experienced a substantial shift over the last several decades in the types of custodial arrangements that are thought to best serve children's interests and upholding their right. The laws in Malaysia similarly uphold this principle but do not provide further deliberation on the principle itself. The principle is entirely developed by the courts through decided cases. Thus, this paper seeks to discuss the extent of the application of best interest of the child principle in custodial disputes. In doing so, it attempts to provide an overview of the current laws and the approach of the Civil and the Shariah courts in Malaysia in applying the principle and for purposes of comparison, it briefly examines the legislation and the courts practices in Australia on this matter since the country has undergone a substantial development in its child custodial policy and legislation. The purpose is to determine the best standard to be adopted by Malaysia and to propose improvement to the laws whenever appropriate.